Does Impairment of Adult Neurogenesis Contribute to Pathophysiology of Alzheimer's Disease? A Still Open Question - Li Puma, Domenica Donatella; Piacentini, Roberto; Grassi, Claudio (Frontiers in Molecular Neuroscience, 2021)
Adult hippocampal neurogenesis is a physiological mechanism contributing to hippocampal memory formation. Several studies associated altered hippocampal neurogenesis with aging and Alzheimer’s disease (AD). However, whether amyloid-β protein (Aβ)/tau accumulation impairs adult hippocampal neurogenesis and, consequently, the hippocampal circuitry, involved in memory formation, or altered neurogenesis is an epiphenomenon of AD neuropathology contributing negligibly to the AD phenotype, is, especially in humans, still debated. The detrimental effects of Aβ/tau on synaptic function and neuronal viability has been clearly addressed both in in vitro and in vivo experimental models. Until some years ago, studies carried out on in vitro models investigating the action of Aβ/tau on proliferation and differentiation of hippocampal neural stem cells led to contrasting results, mainly due to discrepancies arising from different experimental conditions (e.g. different cellular/animal models, different Aβ and/or tau isoforms, concentrations, and/or aggregation profiles). To date, studies investigating in situ adult hippocampal neurogenesis indicate severe impairment in most of transgenic AD mice; this impairment precedes by several months cognitive dysfunction. Using experimental tools, which only became available in the last few years, research in humans indicated that hippocampal neurogenesis is altered in cognitive declined individuals affected by either mild cognitive impairment or AD as well as in normal cognitive elderly with a significant inverse relationship between the number of newly formed neurons and cognitive impairment. However, despite such information is available, the question whether impaired neurogenesis contributes to AD pathogenesis or a mere consequence of Aβ/pTau accumulation is not definitively answered. Herein, we attempted to shed light on this complex and very intriguing topic by reviewing relevant literature on impairment of adult neurogenesis in mouse models of AD and in AD patients analyzing the temporal relationship between the occurrence of altered neurogenesis and the appearance of AD hallmarks and cognitive dysfunctions.